Comparison of Electromyography Activity of Abdominal Muscles and Hamstrings in Women With Low Back Pain During Different Lifting Positions - Faezeh Zandi; Hamideh Khodaveisi (Islamic Azad University, Hamedan Branch, 2021)
Objective: back pain is one of the most common health problems in different societies, especially in industrialized countries. This study aimed to compare the electromyography activity of abdominal muscles and hamstrings in women with low back pain in different lifting positions.  Methods: The present study was a quasi-experimental and laboratory study. The statistical sample consisted of 10 women with back pain and 10 healthy women for whom using 16-channel EMG system and surface electrode, electromyography activity of the right muscles (Rectus Abdominis, Internal Abdominis, External Abdominis, and Biceps Femoris muscle and semitendinosus) while lifting with three Squat, Stoop and freestyle methods were recorded. Data analysis was performed using SPSS software. Analysis of variance was performed by repeated measures and independent t-test at a significant level (P≤0.05). Results: In the stage of lifting weight, the Internal Abdominalis muscle, healthy individuals were more active in the squat technique than in Frees and Stoops, and the patients, Semitendinosus muscle was less involved in the freestyle technique than in the squat technique, but in lowering, weight Semitendinosus muscle of back-pain patients showed more activity in freestyle technique.  Conclusion: In the present study, the freestyle method in patients with back pain is safer for lifting the load than the other two methods. Also, for sports rehabilitation in people with back pain, special attention should be paid to the role and strengthening of the hamstring muscles so that the patient has better performance for lifting activities.